Business letters maker ([s.n.] : Tradetouch.com, Inc, 2004)
Business letters maker includes more than 1000 typical business letter templates.
Ελάχιστες απαιτήσεις συστήματος: Windows 9X/ME/NT/2000/XP.
Keywords: CD-ROMs.; Commercial correspondence -- CD-ROMs.; Letter -- writting -- CD-ROMs.